Difference between revisions of "009B Sample Final 1, Problem 4"

From Math Wiki
Jump to navigation Jump to search
(Created page with "<span class="exam"> Compute the following integrals. <span class="exam">a) <math>\int e^x(x+\sin(e^x))~dx</math> <span class="exam">b) <math>\int \frac{2x^2+1}{2x^2+x}~dx</m...")
 
Line 1: Line 1:
 
<span class="exam"> Compute the following integrals.
 
<span class="exam"> Compute the following integrals.
  
<span class="exam">a) <math>\int e^x(x+\sin(e^x))~dx</math>
+
::<span class="exam">a) <math>\int e^x(x+\sin(e^x))~dx</math>
  
<span class="exam">b) <math>\int \frac{2x^2+1}{2x^2+x}~dx</math>
+
::<span class="exam">b) <math>\int \frac{2x^2+1}{2x^2+x}~dx</math>
  
<span class="exam">c) <math>\int \sin^3x~dx</math>
+
::<span class="exam">c) <math>\int \sin^3x~dx</math>
  
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
Line 12: Line 12:
 
|Recall:
 
|Recall:
 
|-
 
|-
|'''1.''' Integration by parts tells us that <math style="vertical-align: -12px">\int u~dv=uv-\int v~du</math>.
+
|
 +
::'''1.''' Integration by parts tells us that <math style="vertical-align: -12px">\int u~dv=uv-\int v~du.</math>
 
|-
 
|-
|'''2.''' Through partial fraction decomposition, we can write the fraction &nbsp;<math style="vertical-align: -18px">\frac{1}{(x+1)(x+2)}=\frac{A}{x+1}+\frac{B}{x+2}</math> &nbsp;for some constants <math style="vertical-align: -4px">A,B</math>.
+
|
 +
::'''2.''' Through partial fraction decomposition, we can write the fraction &nbsp;<math style="vertical-align: -18px">\frac{1}{(x+1)(x+2)}=\frac{A}{x+1}+\frac{B}{x+2}</math> &nbsp;
 
|-
 
|-
|'''3.''' We have the Pythagorean identity <math style="vertical-align: -5px">\sin^2(x)=1-\cos^2(x)</math>.
+
|
 +
:::for some constants <math style="vertical-align: -4px">A,B.</math>
 +
|-
 +
|
 +
::'''3.''' We have the Pythagorean identity <math style="vertical-align: -5px">\sin^2(x)=1-\cos^2(x).</math>
 
|}
 
|}
  
Line 33: Line 39:
 
|Now, for the first integral on the right hand side of the last equation, we use integration by parts.  
 
|Now, for the first integral on the right hand side of the last equation, we use integration by parts.  
 
|-
 
|-
|Let <math style="vertical-align: 0px">u=x</math> and <math style="vertical-align: 0px">dv=e^xdx</math>. Then, <math style="vertical-align: 0px">du=dx</math> and <math style="vertical-align: 0px">v=e^x</math>.
+
|Let <math style="vertical-align: 0px">u=x</math> and <math style="vertical-align: 0px">dv=e^xdx.</math> Then, <math style="vertical-align: 0px">du=dx</math> and <math style="vertical-align: 0px">v=e^x.</math>
 
|-
 
|-
 
|So, we have
 
|So, we have
Line 50: Line 56:
 
|Now, for the one remaining integral, we use <math style="vertical-align: 0px">u</math>-substitution.  
 
|Now, for the one remaining integral, we use <math style="vertical-align: 0px">u</math>-substitution.  
 
|-
 
|-
|Let <math style="vertical-align: 0px">u=e^x</math>. Then, <math style="vertical-align: 0px">du=e^xdx</math>.
+
|Let <math style="vertical-align: 0px">u=e^x.</math> Then, <math style="vertical-align: 0px">du=e^xdx.</math>  
 
|-
 
|-
 
|So, we have
 
|So, we have
Line 88: Line 94:
 
|Now, we need to use partial fraction decomposition for the second integral.
 
|Now, we need to use partial fraction decomposition for the second integral.
 
|-
 
|-
|Since <math style="vertical-align: -5px">2x^2+x=x(2x+1)</math>, we let <math>\frac{1-x}{2x^2+x}=\frac{A}{x}+\frac{B}{2x+1}</math>.
+
|Since <math style="vertical-align: -5px">2x^2+x=x(2x+1),</math> we let  
 +
|-
 +
|
 +
::<math>\frac{1-x}{2x^2+x}=\frac{A}{x}+\frac{B}{2x+1}.</math>
 +
|-
 +
|Multiplying both sides of the last equation by <math style="vertical-align: -5px">x(2x+1),</math> we get
 +
|-
 +
|
 +
::<math style="vertical-align: -5px">1-x=A(2x+1)+Bx.</math>
 
|-
 
|-
|Multiplying both sides of the last equation by <math style="vertical-align: -5px">x(2x+1)</math>,  
+
|If we let <math style="vertical-align: 0px">x=0</math>, the last equation becomes
 
|-
 
|-
|we get <math style="vertical-align: -5px">1-x=A(2x+1)+Bx</math>.
+
|
 +
::<math style="vertical-align: -1px">1=A.</math>
 
|-
 
|-
|If we let <math style="vertical-align: 0px">x=0</math>, the last equation becomes <math style="vertical-align: -1px">1=A</math>.
+
|If we let <math style="vertical-align: -14px">x=-\frac{1}{2},</math> then we get &thinsp;<math style="vertical-align: -13px">\frac{3}{2}=-\frac{1}{2}\,B.</math> Thus,
 
|-
 
|-
|If we let <math style="vertical-align: -14px">x=-\frac{1}{2}</math>, then we get &thinsp;<math style="vertical-align: -13px">\frac{3}{2}=-\frac{1}{2}\,B</math>. Thus, <math style="vertical-align: 0px">B=-3</math>.
+
|
 +
::<math style="vertical-align: 0px">B=-3.</math>
 
|-
 
|-
|So, in summation, we have&thinsp; <math>\frac{1-x}{2x^2+x}=\frac{1}{x}+\frac{-3}{2x+1}</math>.
+
|So, in summation, we have&thinsp;  
 +
|-
 +
|
 +
::<math>\frac{1-x}{2x^2+x}=\frac{1}{x}+\frac{-3}{2x+1}.</math>
 
|}
 
|}
  
Line 119: Line 138:
 
|For the final remaining integral, we use <math style="vertical-align: 0px">u</math>-substitution.  
 
|For the final remaining integral, we use <math style="vertical-align: 0px">u</math>-substitution.  
 
|-
 
|-
|Let <math style="vertical-align: -2px">u=2x+1</math>. Then, <math style="vertical-align: 0px">du=2\,dx</math> and&thinsp; <math style="vertical-align: -14px">\frac{du}{2}=dx</math>.
+
|Let <math style="vertical-align: -2px">u=2x+1.</math> Then, <math style="vertical-align: 0px">du=2\,dx</math> and&thinsp; <math style="vertical-align: -14px">\frac{du}{2}=dx.</math>
 
|-
 
|-
 
|Thus, our final integral becomes
 
|Thus, our final integral becomes
Line 143: Line 162:
 
!Step 1: &nbsp;  
 
!Step 1: &nbsp;  
 
|-
 
|-
|First, we write <math style="vertical-align: -13px">\int\sin^3x~dx=\int \sin^2 x \sin x~dx</math>.
+
|First, we write <math style="vertical-align: -13px">\int\sin^3x~dx=\int \sin^2 x \sin x~dx.</math>
 
|-
 
|-
|Using the identity <math style="vertical-align: -2px">\sin^2x+\cos^2x=1</math>, we get <math style="vertical-align: -1px">\sin^2x=1-\cos^2x</math>.
+
|Using the identity <math style="vertical-align: -2px">\sin^2x+\cos^2x=1</math>, we get  
 +
|-
 +
|
 +
::<math style="vertical-align: -1px">\sin^2x=1-\cos^2x.</math>  
 
|-
 
|-
 
|If we use this identity, we have
 
|If we use this identity, we have
 
|-
 
|-
| &nbsp; &nbsp; <math style="vertical-align: -13px">\int\sin^3x~dx=\int (1-\cos^2x)\sin x~dx</math>.
+
| &nbsp; &nbsp; <math style="vertical-align: -13px">\int\sin^3x~dx=\int (1-\cos^2x)\sin x~dx.</math>
|-
 
|
 
 
|}
 
|}
  
Line 157: Line 177:
 
!Step 2: &nbsp;
 
!Step 2: &nbsp;
 
|-
 
|-
|Now, we proceed by <math>u</math>-substitution. Let <math>u=\cos x</math>. Then, <math style="vertical-align: -1px">du=-\sin x dx</math>.
+
|Now, we proceed by <math>u</math>-substitution. Let <math>u=\cos x.</math> Then, <math style="vertical-align: -1px">du=-\sin x dx.</math>  
 
|-
 
|-
 
|So we have
 
|So we have

Revision as of 12:03, 18 April 2016

Compute the following integrals.

a)
b)
c)
Foundations:  
Recall:
1. Integration by parts tells us that
2. Through partial fraction decomposition, we can write the fraction    
for some constants
3. We have the Pythagorean identity

Solution:

(a)

Step 1:  
We first distribute to get
Now, for the first integral on the right hand side of the last equation, we use integration by parts.
Let and Then, and
So, we have
Step 2:  
Now, for the one remaining integral, we use -substitution.
Let Then,
So, we have

(b)

Step 1:  
First, we add and subtract from the numerator.
So, we have
Step 2:  
Now, we need to use partial fraction decomposition for the second integral.
Since we let
Multiplying both sides of the last equation by we get
If we let , the last equation becomes
If we let then we get   Thus,
So, in summation, we have 
Step 3:  
If we plug in the last equation from Step 2 into our final integral in Step 1, we have
Step 4:  
For the final remaining integral, we use -substitution.
Let Then, and 
Thus, our final integral becomes
Therefore, the final answer is

(c)

Step 1:  
First, we write
Using the identity , we get
If we use this identity, we have
   
Step 2:  
Now, we proceed by -substitution. Let Then,
So we have
Final Answer:  
(a)  
(b)  
(c)  

Return to Sample Exam